Gastroesophageal reflux disease is associated with abnormal ventricular repolarization indices - Kaya, Hakan; Barutçu, Sezgin (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Gastroesophageal Reflux Disease (GERD) is a clinical entity affecting the upper gastrointestinal tract. The pathophysiology of GERD has been associated with autonomic nervous system disorders. Autonomic nervous system disturbances in GERD patients have been shown to lead to fatal ventricular arrhythmias (VAs) that result in electrical and ventricular repolarization anomalies. The maximum to terminal electrocardiographic T wave (Tpe) has been associated with repolarization of transmural dispersion. In addition, a higher Tpe interval (TpeI) and Tpe/QT ratio correspond with VAs. The goal of this report was to assess ventricular repolarization, by TpeI and Tpe/QT ratio, in GERD patients. Materials and Methods: The study was comprised of 46 GERD subjects and 43 healthy volunteers. TpeI, cTpe, and Tpe/Q ratios were determined from electrocardiograms and associations of the groups were compared. Results: The clinical characteristics were similar between the two groups. TpeI, corrected Tpe (cTpe) interval, and Tpe/QT ratio were higher in subjects with GERD in comparison to the control group (P<0.001, P=0.018, and P<0.001, respectively). Conclusion: TpeI and Tpe/QT ratio were higher in GERD patients. Patients with GERD may have an increased risk for VAs